A Geocoupling Simulation Method for Fractured Reservoir Production. (23rd September 2022) - Li, Xin; Lei, Zhengdong; Zhang, Qinghui; Zhang, Yuanqing
Abstract : Reservoir simulation is critical to the design of reservoir development plan and has been extensively used. However, it is challengeable for to simulate the production process for fractured reservoirs, because of the fracture geometry and the fracture deformation. Specifically, three problems need to be solved. First, there is a lack of mathematical models that can predict the fracture deformation with acceptable precision. Second, the fracture deformation is stress-dependent; therefore, a geocoupled equation should be used to quantify the stress change, but the solution is extremely expensive. Third, the fracture geometries pose great challenges to traditional gridding techniques. This paper proposes a new geocoupling simulation method that is capable of modeling the complex fracture geometry as well as the fracture mechanical behavior. The geomechanical effects and the reservoir production performance are modeled through an implicit geocoupled model, which is developed based on the poro-mechanics theory. The fixed stress strategy is used to solve the geocoupled equations. Moreover, a comprehensive fracture modeling method is proposed, in terms of the fracture deformation model and the fracture gridding technique to model the fracture effects. Ultimately, this method is used to analyze two field-scale cases. The results demonstrate that this method exhibits good practicability and has practical significance for fractured reservoir development.